Biochemical Characterization of A Novel Thermophilic Esterase Isolated from Shewanella sp F88 - A. Asoodeh (Journal of Sciences, Islamic Republic of Iran)
The main objective of this study was to purify and characterize an esterase from Shewanella sp F88. The enzyme was purified 41-fold and an overall yield of 21 %, using a two-step procedure, including ammonium sulfate precipitation and Q-sepharore chromatography. Molecular weight of the enzyme was 62.3 kDa according to SDS-PAGE data. The enzyme showed an optimum activity at pH 6.5 and 58 ˚C. Evolution of substrate specificity demonstrated that this thermostable enzyme had the highest activity towards para-nitrophenol acetate (pNPA, C2). Michaelis-Menten constant (Km) and maximum velocity (Vmax) of pNPA-hydrolyzing reaction were 12.6 mM and 550 U.mg-1, respectively. Enzyme activity was declined in the presence of metal ions (2 and 5 mM), including Fe2+, Ca2+, Cu2+, Zn2+, Mg2+ and Mn2+. The half-lives of purified esterase was 70 and 31 min at 60 °C and 80 °C, respectively. In conclusion, the enzyme is a novel thermostable lipolytic enzyme characterized from Shewanella species.